Effects of humorous interventions on the willingness to donate organs: a quasi-experimental study in the context of medical cabaret - Lisa Heitland; Eckart von Hirschhausen; Florian Fischer (BMC, 2020)
Abstract Background It has been shown that fears and misconceptions negatively affect the willingness to donate organs. Empirical studies have examined health communication strategies that serve to debunk these fears. There are promising indications that humor has the potential to influence health-related attitudes and behaviors. This study examines empirically whether medical cabaret, as a specific format for delivering health-related information in a humorous way, affects the willingness to donate organs. Methods A quasi-experimental study was conducted among the audience of a medical cabaret live show. Participants in two intervention groups and one control group were interviewed just before the start of the live show (t0) and about 6 weeks later (t1). Intervention group 1 (I1) witnessed a ten-minute sequence by the cabaret artist about organ donation. Participants in I2 witnessed the sequence and, in addition, received an organ donor card. Descriptive statistics and t-tests were used to investigate changes in attitudes and the willingness to donate organs from t0 to t1. Results A significant increase in the willingness to donate organs and an improvement in general attitude was observed in the intervention groups. Moreover, significantly more participants in I2 carried an organ donor card after the intervention. Some fears could be reduced, while understanding of the reasons for organ donation could be increased via the intervention. Conclusions The study confirms that medical cabaret is able to affect respondents' attitudes and behaviors even in the context of organ donation. Medical cabaret can enhance the willingness to donate organs and dispel negative concerns.